Johnny English. 3 movie collection [videorecording (DVD)]. - West, Dominic, 1969-; Pike, Rosamund, 1979-; Atkinson, Rowan; Imbruglia, Natalie; Miller, Ben; Anderson, Gillian, 1968-; Malkovich, John; Hennessy, Miranda; Dance, Charles; Howitt, Peter, 1957-; Parker, Oliver; Davies, William (Screenwriter); et al. (Univeral Studios, 2019)
Johnny English: Working for the MI7 agency, Johnny English is suddenly promoted to super spy after Agent One is assassinated and every other agent is blown up at his funeral. When entrepreneur Sauvage sponsors an exhibition of the Crown Jewels and the valuable gems disappear on the opening night, the newly designated agent must jump into action. Tracking the thieves' underground escape route, English locks in on Sauvage despite repeated assurances by boss Pegasus that the respected entrepreneur has nothing to do with the crime.